Reduced diffusion in white matter after radiotherapy with photons and protons - Dünger, L.; Seidlitz, A.; Jentsch, C.; Platzek, I.; Kotzerke, J.; Beuthien-Baumann, Bettina; Baumann, Michael; Krause, Mechthild; Troost, Esther Gera Cornelia; Raschke, F. (Radiotherapy and oncology, 2021)
Background and purpose - Radio(chemo)therapy is standard in the adjuvant treatment of glioblastoma. Inevitably, brain tissue surrounding the target volume is also irradiated, potentially causing acute and late side-effects. Diffusion imaging has been shown to be a sensitive method to detect early changes in the cerebral white matter (WM) after radiation. The aim of this work was to assess possible changes in the mean diffusivity (MD) of WM after radio(chemo)therapy using Diffusion-weighted imaging (DWI) and to compare these effects between patients treated with proton and photon irradiation. - Materials and methods - 70 patients with glioblastoma underwent adjuvant radio(chemo)therapy with protons (n = 20) or photons (n = 50) at the University Hospital Dresden. MRI follow-ups were performed at three-monthly intervals and in this study were evaluated until 33 months after the end of therapy. Relative white matter MD changes between baseline and all follow-up visits were calculated in different dose regions. - Results - We observed a significant decrease of MD (p < 0.05) in WM regions receiving more than 20 Gy. MD reduction was progressive with dose and time after radio(chemo)therapy (maximum: −7.9 ± 1.2% after 24 months, ≥50 Gy). In patients treated with photons, significant reductions of MD in the entire WM (p < 0.05) were seen at all time points. Conversely, in proton patients, whole brain MD did not change significantly. - Conclusions - Irradiation leads to measurable MD reduction in white matter, progressing with both increasing dose and time. Treatment with protons reduces this effect most likely due to a lower total dose in the surrounding white matter. Further investigations are needed to assess whether those MD changes correlate with known radiation induced side-effects.
Gesehen am 30.12.2021